Developing a fair currency system - Muhammad Hanif (ISRA International Journal of Islamic Finance, 2020)
Purpose: This study aims to evaluate the role of the prevailing currency systems in achieving (or departing from) the socio-economic objectives of a progressive and just society; i.e. featuring stability and equitable distribution of wealth. Design/methodology/approach After documenting historical developments in currency systems, the study reviews the Islamic perspective on the matter. Features of an ideal currency system are listed and then a critical evaluation of existing currency systems – fiat, banking and cryptocurrency – is undertaken. Findings It is found that existing currency systems – fiat, banking and cryptocurrency – are not compatible with the socio-economic objectives of a forward-looking, progressive society, which upholds transparency and justice as its core values. The study documents that Sharīʿah norms have no preference or dislike for any of the existing currency systems. Any prudent currency system compatible with the objectives of the Islamic financial system (i.e. stability and equitable distribution of wealth) is acceptable. A single international reserve currency (with country-specific legal tendering) is subject to the risk of destabilisation across global markets. Practical implications This paper recommends autonomy of central banking, the spending of seigniorage for the welfare of community members, development of asset-backed currencies (following ṣukūk structures), as well as multiple international reserve currencies and joining of hands by professionals and Sharīʿah scholars to design a currency system compatible with the Islamic financial system. This paper's recommendation is against the adoption of cryptocurrency that lacks the backing of real assets. Originality/value The study contributes to the literature by evaluating the compatibility of existing currency systems in the achievement of socio-economic objectives of a welfare state which seeks to uphold justice and equitable resource distribution as core values in the financial system.
Keywords: 330; Cryptocurrency; Fiat currency; International currency; Islamic currency